Differences in monthly variation, cause, and place of injury between femoral neck and trochanteric fractures: 6-year survey (2008–2013) in Kyoto prefecture, Japan - Horii, Motoyuki (Clin Cases Miner Bone Metab, 2016)
BACKGROUND: The incidence of femoral neck and trochanteric fractures reportedly differ by age and regionality. We investigated differences in monthly variations of the occurrence of femoral neck and trochanteric fractures as well as place and cause of injury in the Kyoto prefecture over a 6-year period. METHODS: Fracture type (neck or trochanteric fracture), age, sex, place of injury, and cause of injury were surveyed among patients aged ≥ 65 years with hip fractures that occurred between 2008 and 2013 who were treated in 1 of 13 participating hospitals (5 in an urban area and 8 in a rural area). The proportion of sick beds in the participating hospitals was 24.7% (4,151/16,781). Monthly variations in the number of patients were investigated in urban and rural areas in addition to the entire Kyoto prefecture. Place of injury was classified as indoors or outdoors, and cause of injury was categorized as simple fall, accident, or uncertain. RESULTS: There were 2,826 patients with neck fractures (mean age, 82.1 years) and 3,305 patients with trochanteric fractures (mean age, 85.0 years). There were similarities in the monthly variation of the number of fractures in addition to the place and cause of injury between neck and trochanteric fractures. Indoors (approximately 74%) and simple falls (approximately 78%) were the primary place and cause of injury, respectively. The place of injury was not significantly different by fracture type with each age group. Significantly more patients with neck fracture had “uncertain” as the cause of injury than trochanteric fracture in all age groups. CONCLUSIONS: Based on the results of the present study, the injury pattern might not have a great effect on the susceptibility difference between neck and trochanteric fractures.